Community matters: barriers and opportunities to sexual health and sexuality education of young female migrants in Hong Kong - Kwok, Kim; Kwok, Diana K. (Frontiers in Psychology, 2023)
Female migrant workers form a substantial portion of the global migrant workforce and research indicates they are vulnerable to sexual exploitation and barriers to sexual and reproductive healthcare. This article investigates the perceptions, barriers and opportunities to sexual health and sexuality education experienced by young female migrants in Hong Kong. The study adopted a rights-based perspective, employing qualitative methods for data collection, including focus group discussions and semi-structured interviews with 22 female migrants working as domestic workers. Results indicate that young migrants’ perceptions of sexual health behaviors and access to sexuality education are shaped by various interconnected factors at four distinct levels: individual, interpersonal, social and community, and sociocultural and sociopolitical. The present study adds to the existing literature by shedding light on certain perspectives that have not been given due emphasis in comparable studies. First, it highlights the importance of migrant community as barrier as well as opportunity in promoting positive health-seeking behaviors in a culturally acceptable manner. Second, it underscores the interplay between structural forces and individual and group-level vulnerability, emphasizing the need to address structural factors to eliminate young migrants’ internalized vulnerability. Third, it draws attention to the positive dimensions of sexual experiences as a motivator for proactive health-seeking and the intricate relationship between cultural practices and positive sexuality. This article recommends a proactive approach of migrant communities to address sexual healthcare issues while public healthcare institutions should proactively provide accessible sexual healthcare information and services.